ANALISIS STRATEGI PEMASARAN PRODUK UNGGULAN DENGAN PENDEKATAN MARKETING DAN BUSINESS INTELLIGENCE DI KABUPATEN WONOSOBO - Almeira Renata; Mahfudz Mahfudz (Diponegoro Journal of Management, 2023)
ABSTRACT Marketing and business intelligence approaches in this study were used to obtain information and develop the potential of leading sectors in Wonosobo Regency. The object of research used in this study is 15 sub-districts. This study aims to determine the potential of the leading sector. The research method used in this study is the Analytical Hierarchy Process (AHP). The AHP method is used in this study because it is considered capable of producing decisions in order to achieve goals based on the criteria set in the AHP model. Moreover, the strategy and policy used in developing the potential of the leading sector are to collect information from the market or the community as a supporter of the marketing and business intelligence approach, in accordance with the potential of the leading sector owned by each sub-district. Based on the research, the result shows that 15 sub-districts in Wonosobo Regency with details as follows are 7 sub-districts consisting of Garung, Kalikajar, Kaliwiro, Leksono, Selomerto, Sukoharjo, and Watumalang which have the potential of leading agricultural sectors. Then there are 5 sub-districts that have processing potential consisting of Kepil, Kertek, Mojotengah, Sapuran, and Wonosobo. Meanwhile, the subdistricts that have excellent potential in the tourism sector are Kalibawang, Kejajar, and Wadaslintang sub-districts.